Chickpea Biofortification for Cytokinin Dehydrogenase via Genome Editing to Enhance Abiotic-Biotic Stress Tolerance and Food Security - Rohit Kumar Mahto; Ambika; Charul Singh; B S. Chandana; Rajesh Kumar Singh; Shruti Verma; Vijay Gahlaut; Murli Manohar; Neelam Yadav; Rajendra Kumar (Frontiers in Genetics, 2022)
Globally more than two billion people suffer from micronutrient malnutrition (also known as “hidden hunger”). Further, the pregnant women and children in developing nations are mainly affected by micronutrient deficiencies. One of the most important factors is food insecurity which can be mitigated by improving the nutritional values through biofortification using selective breeding and genetic enhancement techniques. Chickpea is the second most important legume with numerous economic and nutraceutical properties. Therefore, chickpea production needs to be increased from the current level. However, various kind of biotic and abiotic stresses hamper global chickpea production. The emerging popular targets for biofortification in agronomic crops include targeting cytokinin dehydrogenase (CKX). The CKXs play essential roles in both physiological and developmental processes and directly impact several agronomic parameters i.e., growth, development, and yield. Manipulation of CKX genes using genome editing tools in several crop plants reveal that CKXs are involved in regulation yield, shoot and root growth, and minerals nutrition. Therefore, CKXs have become popular targets for yield improvement, their overexpression and mutants can be directly correlated with the increased yield and tolerance to various stresses. Here, we provide detailed information on the different roles of CKX genes in chickpea. In the end, we discuss the utilization of genome editing tool clustered regularly interspaced short palindromic repeats/CRISPR associated protein 9 (CRISPR/Cas9) to engineer CKX genes that can facilitate trait improvement. Overall, recent advancements in CKX and their role in plant growth, stresses and nutrient accumulation are highlighted, which could be used for chickpea improvement.